#BJPsych and social media – likes, followers and leading?. (May 2019) - Harrison, Judith R.; Hayes, Joseph F.; Woollard, James; Tracy, Derek K.
Summary: This article explores the growing interface between social media and academic publishing. We discuss how the British Journal of Psychiatry ( BJPsych ) and other scientific journals are engaging with social media to communicate in a digital world. A growing body of evidence suggests that public visibility and constructive conversation on social media networks can be beneficial for researchers and clinicians, influencing research in a number of key ways. This engagement presents new opportunities for more widely disseminating information, but also carries risks. We note future prospects and ask where BJPsych should strategically place itself in this rapidly changing environment. Declaration of interest: J.R.H., J.F.H. and D.T. are on the editorial board of the BJPsych . D.T. runs its social media arm.